Accounting policy as a key tool for achieving financial success and sustainability of a business entity (Economics and region, 2024)
The following issues remain unresolved in the scientific interpretation of the essence of accounting policy: the specificity of accounting policy for different organisational and legal forms and sizes of business entities; and the purpose of accounting policy for management accounting purposes. A clear list and specification of the stages of document development is required, as is the availability of a unified system for modelling accounting policy. This system should be accessible to those responsible for developing such documents, with a view to improving the efficiency of decision-making at different levels.The aim of the research is to improve the theoretical, methodological and organisational support of the process of forming the accounting policy of companies. To achieve this goal, a number of tasks were solved: - Research and disclosure of the definition of accounting policy and its legal support; - list of possible factors influencing the process of accounting policy formation; - study of information support of accounting policy by existing types of accounting; - disclosure of accounting policy as a factor influencing the formation of financial results of any enterprise; - determination of the impact of accounting policy on the financial performance of an entity; - proposals and recommendations for improving accounting policies to improve enterprise management. The scientific novelty of the obtained results lies in improvement of the theoretical, methodological and organisational foundations of the accounting policy of an economic entity and substantiated recommendations on the formation of the Order on Accounting Policy and its use. The obtained results of the scientific work describe information on the practical implementation of proposals for improving the methodology of accounting policy formation, its organisation and legal support.
Keywords: accounting policy; order on accounting policy; enterprise; financial accounting; management accounting; depreciation; reporting; financial results